Familial chilblain lupus: Four cases spanning three generations - Beltoise, A-S; Audouin-Pajot, C; Lucas, P; Tournier, E; Rice, G-I; Crow, Y-J; Mazereeuw-Hautier, J (Annales de dermatologie et de vénéréologie, 2018)
Familial chilblain lupus is a hereditary form of cutaneous lupus erythematosus seen in young children. It shows autosomal dominant inheritance due to mutations in the TREX-1 gene, or, more rarely, SAMHD1 or TMEM173 (STING). It belongs to the type I interferonopathies, i.e. inflammatory diseases associated with excessive interferon production and characterized by a positive "interferon signature". This is a rare entity with fewer than 10 families described to date. We report a new family followed over several years. The patients were four subjects from the same family and spanning three generations (a brother and sister aged 17 and 15 years, their 39-year-old mother, and their 60-year-old grandfather). The initial cutaneous lesions on the extremities were described as papular, erythematous, purplish, infiltrated, hyperkeratotic, pruritic and/or painful. They occurred in childhood, improved during summer and stabilized over time. Immunological abnormalities such as positive antinuclear antibodies were noted. The interferon signature was positive in all patients. Molecular analysis of TREX-1, SAMHD1 and STING genes in both children showed no evidence of mutation. The cutaneous involvement was classic except for absence of the scarring and mutilating progression, photosensitivity and vasculopathy reported in other families. There was no intrafamily variability other than unconstant immunological abnormalities. At the molecular level, no mutations in the known genes were identified. A complementary molecular analysis is in progress. We report a new case of familial LEF, thus adding to knowledge about this very rare form of lupus erythematosus.